ความชุกและปัจจัยที่สัมพันธ์ต่อการติดเชื้อพยาธิเส้นด้ายและพยาธิปากขอสายพันธุ์ที่ติดเชื้อในคนและสายพันธุ์ที่ติดเชื้อในสัตว์เลี้ยงในคนไทยและแรงงานต่างชาติในจังหวัดอุบลราชธานี และคนลาวในแขวงจำปาสัก ประเทศลาว - นันทวดี เนียมนุ้ย (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
Hookworm and threadworm infections are major public health problems in developing countries. A cross-sectional study comprising 843 participants (346 men and 497 women) was conducted in three populations: i) Thai residents (TR) of the Ubol Ratchathani province, Thailand; ii) Laotian immigrant workers (LI) in the same province; and iii) Laotian residents (LR) in Champasak province, Lao PDR. The participants were interviewed based on a structured questionnaire regarding their health status. A total of 300 stool samples from domestic animals (277 dogs and 23 cats) living in the same households with participants were also collected and examined for parasitic infection by Formalin-Ether Concentration Technique and Harada-Mori Filter Paper Culture. The highest prevalence of hookworm infection was found in the LR group (17.5%) followed by LI (11.2%) and TR (4.4%). Meanwhile, highest prevalence of threadworm infection was found in the LI population (19.3%), followed by LR (15.7%) and TR (14.0%). For parasitic diseases in domestic animals from the same households, our results showed that samples from Thailand and Lao PDR contained hookworm eggs at 35.7% and 39.7%, respectively, while the prevalence of threadworm was 0.6% and 1.7%, respectively. We confirmed a case of Ancylostoma ceylanicum infection in a Thai man by PCR and DNA sequencing. Moreover, we also observed other parasites such as Taenia spp and Opisthorchis viverrini. Multivariate analysis indicated that risk factors of hookworm infection were population and walking barefooted. Factors associated with threadworm infection were population, gender, age, previous antiparasitic treatment, knowledge of parasitic infection, and hand washing after contact with domestic animals. Our results highlight the high prevalence of both hookworm and threadworm infections especially among Laotian immigrant workers in Thailand and domestic animals in both countries. Our findings emphasize the need for public health intervention to control the spread of parasitic infections in Thailand and Lao PDR.